Digital Instructional Leadership and Distributed Leadership in Optimizing Teacher Performance through Project-Based Learning Indonesian Value Education - Indrayani, Sari; Sinaga, Risma Margaretha; Rahman, Bujang; Hariri, Hasan; Riswandi, Riswandi; Handoko, Handoko (PPSDP International Journal of Education, 2024)
This study analyzes the contribution of Digital Instructional Leadership (DIL) and Distributed Leadership (DL) in improving teacher performance through the Project-Based Learning (PjBL) approach in the context of Indonesian value education. The research uses a qualitative method with data collection through observation, in-depth interviews, documentation, and focused group discussions. The study found that the implementation of DIL facilitates the integration of digital technology in the learning process, while DL encourages effective collaboration between teachers. Coaching Supervision based on the Ki Hadjar Dewantara Education Trilogy is a key element that mediates the effective implementation of PjBL. However, this study also identifies challenges such as resistance to change, limited technological facilities, and lack of technological competence of teachers. As a solution, it is recommended to strengthen technology training, collaboration between teachers, and intensive supervision support. This research emphasizes the importance of synergy between DIL, DL, and PjBL in creating meaningful learning that instills national values.